Reviews - Lisa Langstraat; Linda T. Calendrillo; Judith Bradshaw-Brown; Frances Jo Grossman (Journal of the Assembly for Expanded Perspectives on Learning, 1996)
Lisa Langstraat. The Epistemic Music of Rhetoric: Toward the Temporal Dimension of Affect in Reader Response and Writing. (Steven B. Katz, 1996). Linda T Calendrillo. Images in Language, Media, and Mind. (Roy F. Fox, Ed., 1994). Judith Bradshaw-Brown. The Tao of Teaching. (Greta Nagel, 1994). Frances Jo Grossman. Bird by Bird: Some Instructions on Writing and Life. (Anne Lamott, 1994)